2016
DOI: 10.1111/jdv.13653
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the mevalonate pathway genes in Chinese patients with porokeratosis

Abstract: This study extended the mutation spectrum of PK in the Chinese Han population and provided further evidence for the genetic basis of PK. We first identified MVD simultaneously responsible for porokeratosis palmaris et plantaris disseminate development and confirmed the genotype-phenotype correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
33
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 16 publications
4
33
0
3
Order By: Relevance
“…The lesions of our patients are consistent with this characteristic. It has been confirmed that the mevalonate pathway is involved in the pathogenesis of porokeratosis …”
mentioning
confidence: 90%
See 3 more Smart Citations
“…The lesions of our patients are consistent with this characteristic. It has been confirmed that the mevalonate pathway is involved in the pathogenesis of porokeratosis …”
mentioning
confidence: 90%
“…Since Zhang et al first identified 14 mutations in MVK (mevalonate kinase) in familial and sporadic DSAP in 2012, MVK mutations have been reported in several cohorts of Chinese patients with DSAP and become the major cause of DSAP. [2][3][4][5] Besides MVK, mutations in MVD (mevalonate decarboxylase) and FDPSgenes in the mevalonate pathwayhave been found to cause DSAP and nonactinic disseminated superficial porokeratosis (DSP). 5,6 To date, only five mutations (c.À1129_141+994del, c.283-1776_649-143del, c.338G>A, c.486+1G>A and c.773+1G>A) in FDPS have been documented in patients with DSAP or DSP.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Gene mutations in mevalonate pathway enzymes, such as mevalonate kinase ( MVK ), phosphomevalonate kinase ( PMVK ), mevalonate decarboxylase ( MVD ), and farnesyl diphosphate synthase ( FDPS ), may be involved in the pathogenesis of PK. [34] In the present study, five sporadic patients with PK were recruited. Dermoscopic features were investigated, and genetic testing was conducted.…”
mentioning
confidence: 99%